COVID-19’s re-bordering impact on the identity of the Polish-German borderland from the perspective of Polish residents: the case of the twin cities of Słubice and Gubin - Rogowski, Łukasz; Frąckowiak, Maciej (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
One of the effects of the COVID-19 pandemic was the temporary closure of many state borders and the reintroduction of border controls. This included countries in the Schengen Area, and thus the Polish-German border. These events can be seen as an example of rebordering processes. They significantly impacted the life of Polish-German twin cities, whose functioning is based mainly on cross-border flows, mobility, and exchange. The paper aims to determine how the temporary border closure affected the Polish-German borderland identity. This is based on qualitative empirical research. The research is comparative in nature and juxtaposes statements collected before (in-depth interviews) and during (phone interviews) the pandemic. On this basis, the identity of the borderland is described in four dimensions: othering, sense of belonging, cultural landscape, and border practices and routines. This made it possible to characterize the impact of the border closure on the local community more comprehensively. Negating the border as a place of exchange, and associating it with a threat, resulted in economic decline and a sense of uprooting. This conclusion should translate into more significant consideration of the identity aspect in public policies designed to address border closures in the EU following the pandemic.